Comparative in vitro cytotoxicity of modified deoxynivalenol on porcine intestinal epithelial cells. (September 2016) - Broekaert, Nathan; Devreese, Mathias; Demeyere, Kristel; Berthiller, Franz; Michlmayr, Herbert; Varga, Elisabeth; Adam, Gerhard; Meyer, Evelyne; Croubels, Siska
Abstract: The gastrointestinal tract is the first target after ingestion of the mycotoxin deoxynivalenol (DON) via feed and food. Deoxynivalenol is known to affect the proliferation and viability of animal and human intestinal epithelial cells. In addition to DON, feed and food is often co-contaminated with modified forms of DON, such as 3-acetyldeoxynivalenol (3ADON), 15-acetyl-deoxynivalenol (15ADON) and deoxynivalenol-3-β-D-glucoside (DON3G). The goal of this study was to determine the in vitro intrinsic cytotoxicity of these modified forms towards differentiated and proliferative porcine intestinal epithelial cells by means of flow cytometry. Cell death was assessed by dual staining with Annexin-V-fluorescein isothiocyanate (FITC) and propidium iodide (PI), which allows the discrimination of viable (FITC−/PI−), apoptotic (FITC+/PI−) and necrotic cells (FITC+/PI+). Based on the data from the presented pilot in vitro study, it is concluded that cytotoxicity for proliferative cells can be ranked as follows: DON3G ≪ 3ADON < DON ≈ 15ADON. Highlights: Flow cytometry with Annexin-V-FITC and PI allowed discrimination of viable, apoptotic and necrotic IPEC-J2 cells. Cytotoxicity for proliferative cells can be ranked as follows: DON3G ≪ 3ADON < DON ≈ 15ADON. Differentiated IPEC-J2 cells are less susceptible to the evaluated mycotoxins compared to their proliferative counterparts.